2019
DOI: 10.1111/imb.12565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the evolution and function of the dynamic Venom Y protein in ectoparasitoid wasps

Abstract: Venom of the parasitoid wasp Nasonia vitripennis changes the metabolism and gene expression in its fly host Sarcophaga bullata to induce developmental arrest, suppression of the immune response and various other venom effects. Yet, the venom of ectoparasitoid wasps has not been fully characterized. A major component of N. vitripennis venom is an uncharacterized, high‐expressing protein referred to as Venom Y. Here we describe the evolutionary history and possible functions of this venom protein. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The main components of this venom [38] include, among others, serine-and metalloproteases, triggering apoptotic processes in Spodoptera frugiperda Sf21 cell line [39], two serpins and another protease inhibitor, interfering with prophenoloxidase activation in the host Musca domestica [40,41], and a chitinase, inducing an upregulation of host genes involved in the immune response against fungi [42]. Additional functional studies will be likely fostered in this research area since N. vitripennis is a powerful model system, for which the genome sequence and molecular tools are available [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…The main components of this venom [38] include, among others, serine-and metalloproteases, triggering apoptotic processes in Spodoptera frugiperda Sf21 cell line [39], two serpins and another protease inhibitor, interfering with prophenoloxidase activation in the host Musca domestica [40,41], and a chitinase, inducing an upregulation of host genes involved in the immune response against fungi [42]. Additional functional studies will be likely fostered in this research area since N. vitripennis is a powerful model system, for which the genome sequence and molecular tools are available [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Only a very small portion of genes of T. molitor pupae changed their transcriptions after this beetle was envenomated with SgVnDPPIV. This is similar to venom Y, a major component of Nasonia vitripennis venom, in that the presence of this venom can only lead to changes of 1.8% of the total genes of its host, flesh fly Sarcophaga bullata [ 41 ]. The majority of them are detoxification, immunity, neural, and fat-body-specific genes [ 41 ].…”
Section: Discussionmentioning
confidence: 97%
“…This is similar to venom Y, a major component of Nasonia vitripennis venom, in that the presence of this venom can only lead to changes of 1.8% of the total genes of its host, flesh fly Sarcophaga bullata [ 41 ]. The majority of them are detoxification, immunity, neural, and fat-body-specific genes [ 41 ]. Among the genes affected by SgVnDPPIV, many of them are involved in oxidation reduction, lipid synthesis and metabolism, response to stimuli, and ion exchange, indicating the corresponding function of SgVnDPPIV.…”
Section: Discussionmentioning
confidence: 97%
“…Knockdown experiments in Nasonia vitripennis revealed that chitinases primarily trigger immune responses that defend the host against fungi ( Martinson et al, 2016 ). In a similar approach, knockdown experiments targeting the N. vitripennis venom component venom Y suggested that its role is the detoxification and mitigation of other venom components, in addition to regulating the host immune system ( Martinson et al, 2019 ). The knockdown of α-amylase in Pteromalus puparum venom negatively affected larval development, suggesting that amylases regulate host metabolism and developmental processes ( Wang et al, 2020a ).…”
Section: Manipulating Genetic Information: Studying Venom Systems By ...mentioning
confidence: 99%